Human restricted CHRFAM7A gene increases brain efficiency - Jakimovski, Dejan; Dorn, Ryu P.; Regno, Megan Del; Bartnik, Alexander; Bergsland, Niels; Ramanathan, Murali; Dwyer, Michael G.; Benedict, Ralph H. B.; Zivadinov, Robert; Szigeti, Kinga (Frontiers in Neuroscience, 2024)
Introduction: CHRFAM7A, a uniquely human fusion gene, has been associated with neuropsychiatric disorders including Alzheimer’s disease, schizophrenia, anxiety, and attention deficit disorder. CHRFAM7A was identified as a potent modulator of intracellular calcium and an upstream regulator of Rac1 leading to actin cytoskeleton reorganization and switch from filopodia to lamellipodia implicating efficient neuronal structure. Methods: Dual locus-specific genotyping of CHRFAM7A was performed on genomic DNA to determine copy number (TaqMan assay) and orientation (capillary sequencing) of the CHRFAM7A alleles. As only the direct allele is expressed at the protein level and affects alpha7 nAChR function, direct allele carriers and non-carriers are compared. Subjects underwent neuropsychological testing to measure cognitive processing speed (Symbol Digit Modalities Test), learning and memory (California Verbal Learning Test and Brief Visuospatial Memory Test – Revised for immediate and delayed recalls), Global and tissue-specific volumes were determined using SIENAX and FIRST algorithms on lesion-inpainted images. Results: CHRFAM7A direct allele carrier and non-carrier groups included 33 and 13 individuals, respectively. Demographic variables were comparable. CHRFAM7A direct allele carriers demonstrated an upward shift in cognitive performance including cognitive processing speed, learning and memory, reaching statistical significance in visual immediate recall (FDR-corrected p=0.018). The shift in cognitive performance was associated with smaller whole brain volume (uncorrected p=0.046) and lower connectivity by resting state functional MRI in the visual network (FDR-corrected p=0.027) accentuating the cognitive findings. Conclusion These data suggest that direct allele carriers harbor a more efficient brain consistent with the cellular biology of actin cytoskeleton and synaptic gain of function.